ENHANCING THE METHODOLOGY FOR DEVELOPING PROFESSIONAL PEDAGOGICAL COMPETENCE OF FUTURE TEACHERS IN DIGITAL TECHNOLOGIES (American Journal of Pedagogical and Educational Research, 2024)
As digital technologies continue to transform various aspects of our lives, it is crucial to equip future teachers with the necessary professional pedagogical competence to effectively integrate digital technologies into their teaching practices. This article aims to explore and propose an improved methodology for enhancing the professional pedagogical competence of future teachers in the discipline of digital technologies. By integrating theoretical frameworks, practical experiences, and evidence-based strategies, this methodology seeks to empower future teachers with the knowledge, skills, and mindset required to navigate the digital landscape and deliver quality education in the digital age. The proposed methodology emphasizes a holistic approach, encompassing both theoretical understanding and practical application, and highlights the importance of ongoing professional development and reflective practice.